Contributi per una flora vascolare di Toscana. I (1-85) - PERUZZI, LORENZO; BEDINI, GIANNI; VICIANI D (2009)
New localities and/or confirmations concerning 85 specific and subspecific plant taxa of Tuscan vascular flora, belonging to 72 genera and 49 families: Mesembryanthemum (Aizoaceae), Baldellia (Alismataceae), Arthrocnemum (Amaranthaceae), Allium, Narcissus (Amaryllidaceae), Bupleurum, Petroselinum (Apiaceae), Loncomelos (Asparagaceae), Asplenium (Aspleniaceae), Bellis, Cirsium, Filago, Glebionis (Asteraceae), Symphytum (Boraginaceae), Cardamine, Hesperis, Thlaspi (Brassicaceae), Solenopsis (Campanulaceae), Illecebrum, Moenchia (Caryophyllaceae), Colchicum (Colchicaceae), Crassula, Sedum (Crassulaceae), Ecballium (Cucurbitaceae), Cuscuta (Convolvulaceae), Carex, Cladium, Cyperus, Isolepis, Scirpus (Cyperaceae), Hippophaë (Elaeagnaceae), Pyrola (Ericaceae), Euphorbia (Euphorbiaceae), Lathyrus, Ononis (Fabaceae), Cicendia (Gentianaceae), Ribes (Grossulariaceae), Najas (Hydrocharitaceae), Hypericum (Hypericaceae), Romulea (Iridaceae), Isoëtes (Isoëtaceae), Juncus, Luzula (Juncaceae), Ajuga, Stachys, Teucrium (Lamiaceae), Lilium, Tulipa (Liliaceae), Linum (Linaceae), Montia (Montiaceae), Ludwigia (Onagraceae), Ophioglossum (Ophioglossaceae), Spiranthes (Orchidaceae), Osmunda (Osmundaceae), Plantago (Plantaginaceae), Imperata, Micropyrum, Polypogon, Sesleria (Poaceae), Polygala (Polygalaceae), Groenlandia (Potamogetonaceae), Lysimachia (Primulaceae), Pteris (Pteridaceae), Caltha, Ranunculus (Ranunculaceae), Alchemilla, Rosa (Rosaceae), Salix (Salicaceae), Saxifraga (Saxifragaceae), Thelypteris (Thelipteridaceae), Daphne (Thymelaeaceae) and Viola (Violaceae). In the end, the conservation status of the units and eventual protection of the cited biotopes are discussed.